The child's fairy tale book - Chorao, Kay. (New York : Dutton Children's Books, 1990)
A collection of five fairy tales including "Snow White and the seven dwarfs, " "Muchie Lal, " "Rapunzel, " "The Ants That Pushed On The Sky, " and "Cinderella."
Mode of access: Internet.
Keywords: Fairy tales